Research on Performance Evaluation System of Shale Gas PPP Project Based on Matter Element Analysis. (30th October 2018) - Luo, Zhenhua; Yang, Yufan; Pan, Haize; Zhong, Mengfan
Abstract : The PPP model is a Public-Private Partnership and a pattern which provides product or service to the public; applying the PPP model to the shale gas development project helps to solve the difficult problem that exists in the shale gas project. Through extensive literature analysis and in-depth study of shale gas PPP projects, for performance evaluation of shale gas PPP project, based on the five dimensions of macroenvironmental characteristics, economic benefits, the project internal processes, innovation and environmental protection and sustainable development, and stakeholder satisfaction, an indicator system consisting of 22 secondary indicators was set up, and the weight of each index was determined by AHP, using the matter element analysis method to build the comprehensive evaluation of the shale gas PPP project performance evaluation model and set indicator evaluation standard of excellent, good, medium, general, and poor in five grades. We evaluate the performance of a shale gas PPP project and conclude that the evaluation grades of the project are good, which is in line with the reality, indicating that the evaluation system and the method are effective and credible.